COVID-19 as Eco-Pandemic Injustice: Opportunities for Collective and Antiracist Approaches to Environmental Health. (June 2021) - Powers, Martha; Brown, Phil; Poudrier, Grace; Ohayon, Jennifer Liss; Cordner, Alissa; Alder, Cole; Atlas, Marina Goreau
The COVID-19 pandemic has coincided with a powerful upsurge in antiracist activism in the United States, linking many forms and consequences of racism to public and environmental health. This commentary develops the concept of eco-pandemic injustice to explain interrelationships between the pandemic and socioecological systems, demonstrating how COVID-19 both reveals and deepens structural inequalities that form along lines of environmental health. Using Pellow's critical environmental justice theory, we examine how the crisis has made more visible and exacerbated links between racism, poverty, and health while providing opportunities to enact change through collective embodied health movements . We describe new collaborations and the potential for meaningful opportunities at the intersections between health, antiracist, environmental, and political movements that are advocating for the types of transformational change described by critical environmental justice.